1990
DOI: 10.1161/01.str.21.10.1419
|View full text |Cite
|
Sign up to set email alerts
|

Leukoaraiosis, intracerebral hemorrhage, and arterial hypertension.

Abstract: To investigate whether the observed association of leukoaraiosis with intracerebral hemorrhage is direct or mediated by risk factors, we compared 116 patients with intracerebral hemorrhage confirmed by computed tomography and 155 controls without intracerebral hemorrhage, evaluating the prevalence of leukoaraiosis and vascular risk factors. Leukoaraiosis was observed in 21 (18%) of the 116 patients and in 12 (8%) of the 155 controls (p<0.01). Only two (6%) of the 31 patients with lobar hemorrhage had leukoarai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
51
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 38 publications
6
51
0
Order By: Relevance
“…4,12,[16][17][18] However, controlled studies of LA in clinically selected series have revealed the limited importance of hypertension. 11,19 Our results also indicate a limited relationship between hypertension and LA. In association, the duration of hypertension was longer in stroke patients with LA than in stroke patients without LA.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…4,12,[16][17][18] However, controlled studies of LA in clinically selected series have revealed the limited importance of hypertension. 11,19 Our results also indicate a limited relationship between hypertension and LA. In association, the duration of hypertension was longer in stroke patients with LA than in stroke patients without LA.…”
Section: Discussionsupporting
confidence: 47%
“…LA was less associated with hemorrhages, cortical or subcortical infarcts. Inzitari et al 19 have concluded that LA is an independent risk factor for intracerebral hemorrhage. Bogousslavsky et al 17 have found that leuko-encephalopathy was more frequent with deep infarct than with cortical infarct.…”
Section: Discussionmentioning
confidence: 99%
“…22 Leukoaraiosis or white matter ischemic disease (WMD) is a risk factor for ICH, probably because of its association with arterial HTN. 23 The presence of WMD in ICH patients is associated with larger hematoma volume and hematoma expansion. 24 Chronic kidney disease is independently associated with both ischemic and hemorrhagic stroke, though implications for prevention are still to be determined.…”
Section: Introductionmentioning
confidence: 97%
“…However, there is accumulating evidence from population-based studies that LA is associated with an increased risk of stroke and recurrent stroke, depending on the grade of LA that is present. [5][6][7] Furthermore, the progression of LA is also significantly associated with cognitive impairments and dementia of Alzheimer type. [8][9][10][11][12] Thus, LA could be considered as an intermediate surrogate of brain dysfunctions including cerebrovascular damages.…”
Section: Introductionmentioning
confidence: 99%